Emerging molecular alterations leading to histology-specific targeted therapies in ovarian cancer beyond PARP inhibitors. (December 2021) - Bartoletti, M.; Musacchio, L.; Giannone, G.; Tuninetti, V.; Bergamini, A.; Scambia, G.; Lorusso, D.; Valabrega, G.; Mangili, G.; Puglisi, F.; Pignata, S.
Highlights: PARP inhibitors have opened the era of targeted therapy in ovarian cancer; Major therapeutic improvements have been limited to the high grade serous subtype; The panorama of possible clinically actionable targets in ovarian cancer is wider. New druggable alterations and matched drugs are under investigation. Abstract: After more than 30 years of a one-size-fits-all approach in the management of advanced ovarian cancer, in 2018 the SOLO1 trial results have introduced a new era of personalized medicine. A deeper knowledge of ovarian cancer biology and the development of new drugs targeting specific molecular pathways have led to biomarker-driven phase 3 trials with practice changing results. Thereafter, platinum-based combinations are no longer the only therapeutic options available in first line setting and poly-ADP ribose polymerase inhibitors maintenance therapy has become the mainstay in patients with tumor harboring a homologous recombination defect. However, most of the recent therapeutic breakthroughs regard high grade serous carcinoma, the most frequent ovarian cancer subtype, and only few improvements have occurred in the management of less common histotypes. Moving towards the next challenges, we aimed to investigate and review new potential molecular targets in ovarian cancer, according to histotype, starting from promising molecular drivers and matched drugs that have been investigated in early and late-stage clinical trials or conceptualized in preclinical studies.